2023
DOI: 10.1038/s41598-023-35565-y
|View full text |Cite
|
Sign up to set email alerts
|

Pilot evaluation of a single oral fecal microbiota transplantation for canine atopic dermatitis

Abstract: The gut microbiota has been suggested to be involved in the pathogenesis of canine atopic dermatitis (cAD). However, the gut microbiota has not been well characterized in dogs with atopic dermatitis (AD). In addition, the efficacy of fecal microbiota transplantation (FMT) in dogs with AD remains unclear. This research, therefore, aimed to characterize the gut microbiota of dogs with AD and conduct pilot evaluation of the efficacy of a single oral FMT on clinical signs and the gut microbiota of dogs with AD. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
4
9
0
Order By: Relevance
“…This observation is in line with previous studies [ 52 ]. When comparing the gut microbiota in healthy dogs with that in cAD-affected dogs (cADpre), the abundance of Fusobacteria was significantly reduced in cAD-affected dogs, which is in line with previous studies of gut microbiota in dogs affected with cAD and healthy dogs [ 22 , 23 ]. This was further illustrated at the genus level, presenting the reduction of Fusobacterium abundance in cADpre dogs compared with that in healthy dogs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This observation is in line with previous studies [ 52 ]. When comparing the gut microbiota in healthy dogs with that in cAD-affected dogs (cADpre), the abundance of Fusobacteria was significantly reduced in cAD-affected dogs, which is in line with previous studies of gut microbiota in dogs affected with cAD and healthy dogs [ 22 , 23 ]. This was further illustrated at the genus level, presenting the reduction of Fusobacterium abundance in cADpre dogs compared with that in healthy dogs.…”
Section: Discussionsupporting
confidence: 89%
“…This is considered to be a similar situation for the clinical management of cAD. While several studies of gut microbiota in cAD-affected dogs have recently been reported; a pilot study using a limited number of Beagles [ 21 ] and one breeding colony of Shiba Inu dogs [ 22 ], or a study of multiple dog breeds [ 23 ], no studies dissecting both skin gut microbiota in cAD-affected dogs are available to date.…”
Section: Introductionmentioning
confidence: 99%
“…Sugita et al. ( 2023 ) reported that the gut microbiota plays a pivotal role in the pathogenesis of canine atopic dermatitis and that oral faecal microbiota transplantation may be a novel therapeutic approach to target the gut microbiota in canine atopic dermatitis. Similarly, K. Ural ( 2022 ) reported that faecal microbiota transplantation capsules were beneficial in the treatment of canine atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review demonstrated that while nearly half of included studies reported a positive effect of an altered gut microbial colonization due to the use of probiotics on the severity of AD, other studies did not observe such effect ( 13 ). Recently, animal studies have found that FMT treatment benefits mice or dogs with AD by enhanccing gut microbiota homeostasis ( 7 , 14 16 ). In 2022, Mashiah et al.…”
Section: Discussionmentioning
confidence: 99%